Exploring mathematics with scientific notebook - Yang, Wei-Chi.; Lewin, Jonathan ([S.l.] : Springer, 1998)
Scientific Notebook is the latest gateway to interactive teaching and learning in the sciences and is a uniquely user- friendly front end to the computing engine Maple. As such, it provides a powerful new writing and computing tool for scientists, students and teachers alike. Exploring Mathematics with Scientific Notebook describes the use of Scientific Notebook and presents several innovative approaches to scientific computing and to teaching pedagogy that exploit its special features. This book contains a number of separate modules that are designed as supplements to the standard bill of fare in the study of algebra, calculus, linear algebra, analysis, and other topics in an undergraduate mathematics curriculum. Each module provides the student with a truly interactive environment and encourages him to experiment with the material and explore a variety of possibilities. Some of the modules contain animations of two or three dimensional graphs that can be run with a single click of a mouse and which provide even greater insight into the mathematics contained in them. This hard copy bound version of the book is a companion to the on-screen version that is contained in the CD-ROM that is included with each copy of the book and which also includes a time-locked copy of the software product Scientific Notebook. The book and the software are easy to install and to use, and instructors will find in them a refreshing new approach that opens up a new world of innovative and creative thinking for students in an undergraduate mathematics curriculum.
Keywords: Mathematics; Data processing; Scientific Notebook